DEVELOPMENT AND VALIDATION OF A GAS CHROMATOGRAPHY HEADSPACE METHOD FOR THE SIMULTANEOUS QUANTIFICATION OF SIX ORGANIC VOLATILE IMPURITIES IN SUMATRIPTAN SUCCINATEAPI AND ITS PHARMACEUTICAL DOSAGE FORMS - KISHORE J, KRISHNA; RAO K, PRASADA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The main aim of this study, to develop a validated analytical method for simultaneous quantification of six organic volatile impurities (OVI) in sumatriptan succinate active pharmaceutical ingredients (API) and its pharmaceutical dosage forms by headspace (HS)-gas chromatography (GC). Methods: The method development and its validation were performed on a Shimadzu GC-2010 GC system equipped with a flame ionization detector and Teledynetekmar HT3TM HS analyzer. The method involved a thermal gradient elution of six OVI present in sumatriptan succinate API. DB-624, 30 m×0.53 mm, 3.0 μ column is used as a stationary phase and nitrogen gas is used as a carrier gas. The flow rate was 2.8 mL/min and the flame ionization detector temperature is 260°C. Results: The correlation coefficient (r2) was not <0.99 at the limit of quantification (LOQ) to 150%. The limit of detection obtained for methanol, acetone, isopropyl alcohol, dichloromethane, benzene, and toluene was found 18.4, 8.8, 5.5, 4.3, 0.04, and 4.2 ppm. The LOQ obtained was 55.8, 26.8, 16.6, 13.0, 0.1, and 12.6 ppm. Accuracy results were obtained from 85 to 115% for six OVI’s. Furthermore, verified precision, ruggedness, robustness, solution stability, and pharmaceutical analysis. All the results are found within the acceptable limits. Conclusion: The method presents a simple and reliable solution for the routine quantitative analysis of organic volatile impurities present in sumatriptan succinate API.